Agmatine, a metabolite of L-arginine, reverses scopolamine-induced learning and memory impairment in rats - ARICIOĞLU, FEYZA (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Agmatine (1-amino-4-guanidino-butane), a metabolite of L-arginine through the action of arginine decarboxylase, is a novel neurotransmitter. In the present study, effects of agmatine on cognitive functions have been evaluated by using one trial step-down passive avoidance and three panel runway task. Agmatine (20, 40, 80 mg/kg i.p.) was administered either in the presence or absence of a cholinergic antagonist, scopolamine (1 mg/kg i.p.). Scopolamine significantly impaired learning and memory in both passive avoidance and three panel runway test. Agmatine did not affect emotional learning, working and reference memory but significantly improved scopolamine-induced impairment of learning and memory in a dose dependent manner. Our results indicate that agmatine, as an endogenous substance, may have an important role in modulation of learning and memory functions. (c) 2012 Elsevier Inc. All rights reserved.
Keywords: Agmatine; Scopolamine; Cognition; Three panel runway; Passive avoidance; NITRIC-OXIDE SYNTHASE; MORPHINE-WITHDRAWAL; CEREBRAL-ISCHEMIA; INDUCED SEIZURES; L-CITRULLINE; BRAIN; INVOLVEMENT; MODULATION; GLUTAMATE; WORKING